2012
DOI: 10.1024/1422-4917/a000200
|View full text |Cite
|
Sign up to set email alerts
|

Übereinstimmung von klinischer Diagnose, strukturierten Interviews und Selbstbeurteilungsfragebögen bei Depression im Kindes- und Jugendalter

Abstract: Clinicians may profit from conducting structured interviews. Strategies for dealing with conflicting information from children and parents should be tested empirically and described in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…Results of the present study further support the use of structured interviews in clinical practice. The results of Dolle, Schulte‐Körne, von Hofacker, Izat, and Allgaier () on the low agreement between clinical diagnoses and diagnoses based on structured interviews also emphasize the application of structured interviews in the diagnostic process in clinical practice.…”
Section: Discussionmentioning
confidence: 95%
“…Results of the present study further support the use of structured interviews in clinical practice. The results of Dolle, Schulte‐Körne, von Hofacker, Izat, and Allgaier () on the low agreement between clinical diagnoses and diagnoses based on structured interviews also emphasize the application of structured interviews in the diagnostic process in clinical practice.…”
Section: Discussionmentioning
confidence: 95%
“…The inconsistency was attributed to both over and under reporting by parents (Lauth et al, 2010). Similarly, in another study, Dolle et al (2012) reported low agreement between child and parent diagnostic interviews. De Los Reyes and Kazdin (2005) reviewed studies seeking to identify informant characteristics that influence such discrepancies and found that parent proxy report on adolescent mental health symptoms is often biased.…”
Section: Introductionmentioning
confidence: 83%
“…Dabei ist Kappa jedoch von der Sensitivität und Spezifität der jeweiligen Beurteilung sowie von der Prävalenz des festgestellten Störungsbildes abhängig. So fällt Kappa bei mangelhafter Güte der Beurteilung geringer aus und nähert sich bei sehr hohen oder sehr niedrigen Prävalenzen dem Wert null [Thompson und Walter, 1988;Dolle et al, 2012].…”
Section: Statistische Auswertungunclassified